Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence 2021
DOI: 10.24963/ijcai.2021/203
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Heterogeneous Information Network Embedding

Abstract: Heterogeneous information network (HIN) embedding, learning the low-dimensional representation of multi-type nodes, has been applied widely and achieved excellent performance. However, most of the previous works focus more on static heterogeneous networks or learning node embedding within specific snapshots, and seldom attention has been paid to the whole evolution process and capturing all temporal dynamics. In order to fill the gap of obtaining multi-type node embeddings by considering all temporal dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The other feasible and commonly used approach is to utilize knowledge graph embedding (KGE) techniques to train a low-dimensional vector for each entity and relation, while maintaining the inherent structure of the IKG. The resulting vectors obtained through KGE can then be utilized to enhance the representations of entities in the IKG [13][14][15][16][17]. However, it is noted that although KGE is specifically tailored for tasks related to knowledge graphs, it is not optimized for applications in industrial settings.…”
Section: Knowledge Graph Embeddingmentioning
confidence: 99%
“…The other feasible and commonly used approach is to utilize knowledge graph embedding (KGE) techniques to train a low-dimensional vector for each entity and relation, while maintaining the inherent structure of the IKG. The resulting vectors obtained through KGE can then be utilized to enhance the representations of entities in the IKG [13][14][15][16][17]. However, it is noted that although KGE is specifically tailored for tasks related to knowledge graphs, it is not optimized for applications in industrial settings.…”
Section: Knowledge Graph Embeddingmentioning
confidence: 99%
“…Although these methods can learn graph dynamics of the THG to some extent, the temporal information within the same snapshot is usually ignored, and the scale of snapshots needs to be predetermined in advance. Recently, researchers have proposed continuous-time dynamic graph (CTDG [14]) approaches [19][20][21][22][23][24] to capture dynamics via passing information between different interactions, or using continuoustime functions to generate temporal embedding. In regard to the new nodes, inductive graph representation learning methods [5,22,23,25] recognize structural features of node neighborhood by learning trainable aggregation functions, so that rapidly generate node embeddings in new subgraphs.…”
Section: Examplementioning
confidence: 99%
“…Recent studies [19][20][21][22][23]30] have shown the superior performance of continuous-time methods in dealing with temporal graphs. JODIE [21] uses RNNs to propagate information in interactions and update node representations smoothly at different timesteps.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…TDGNN [30] introduces a temporal aggregator for GNNs to aggregate historical information of neighbor nodes and edges. Hawkes process [15,60] is also applied to simulate the evolution of graphs. Furthermore, DyRep [40] leverages recurrent neural networks to update node representations over time.…”
Section: Introductionmentioning
confidence: 99%